Cancer‐Associated, Stimuli‐Driven, Turn on Theranostics for Multimodality Imaging and Therapy. Issue 23 (29th March 2017) - Li, Xingshu; Kim, Jihoon; Yoon, Juyoung; Chen, Xiaoyuan
Abstract : Advances in bioinformatics, genomics, proteomics, and metabolomics have facilitated the development of novel anticancer agents that have decreased side effects and increased safety. Theranostics, systems that have combined therapeutic effects and diagnostic capabilities, have garnered increasing attention recently because of their potential use in personalized medicine, including cancer‐targeting treatments for patients. One interesting approach to achieving this potential involves the development of cancer‐associated, stimuli‐driven, turn on theranostics. Multicomponent constructs of this type would have the capability of selectively delivering therapeutic reagents into cancer cells or tumor tissues while simultaneously generating unique signals that can be readily monitored under both in vitro and in vivo conditions. Specifically, their combined anticancer activities and selective visual signal respond to cancer‐associated stimuli, would make these theranostic agents more highly efficient and specific for cancer treatment and diagnosis. This article focuses on the progress of stimuli‐responsive turn on theranostics that activate diagnostic signals and release therapeutic reagents in response to the cancer‐associated stimuli. The present article not only provides the fundamental backgrounds of diagnostic and therapeutic tools that have been widely utilized for developing theranostic agents, but also discusses the current approaches for developing stimuli‐responsive turn on theranostics. Abstract : Recent progress in the development of theranostic systems illustrates the future approach to highly specific and efficient cancer treatment. Novel and interesting theranostics, which can be selectively turned on by cancer‐associated stimuli, have been widely investigated. The results of this effort show the great promise of this approach in clinical applications. Particularly interesting are multimodal imaging‐guided therapy strategies that should play a special and meaningful role in personalized medicine.